Effects of 7-week hip thrust versus back squat resistance training on performance in adolescent female soccer players - González-Garcia, J.; Morencos, E.; Balsalobre-Fernandez, C.; Cuéllar-Rayo, A.; Romero-Moraleda, B. (Sports, 2019)
Hip thrust (HT) is a loaded bridging exercise that requires more hip extension than a back squat (SQ) does, while in a back squat, triple flex extension occurs. Due to the specificity of each exercise, it is claimed that HT gains can be better transferred to actions where hip extension occurs. In addition, strength improvements during squatting can be transferred in a greater way to vertical plane movement, such as vertical jumping. However, its effects on the performance of female soccer players are unclear. For this reason, the purpose of this study was to analyze a 7-week training program on performance variables using either HT or SQ exercises in female adolescent soccer players without lifting experience (N = 24, age = 16.82 ± 1.56 years, height = 1.64 ± 0.55 cm, body mass = 58.35 ± 6.28 kg). Players were randomized into three groups: A back squat group (SQG; N = 8), hip thrust group (HTG; N = 8), and control group (CG; N = 8). Participants in the HTG and SQG joined a progressive resistance training program twice per week for 7 weeks with either HT or SQ exercises. A countermovement jump, 10-20 m sprint, T-test, and barbell velocity during HTs and SQs (with the load that represents ~60 and ~80% RM) were measured before and after the intervention. The HTG showed greater improvements in the 10-m sprint (d = 0.7), 20-m sprint (d = 0.46), T-test (d = 0.36), and barbell velocity at 80% repetition maximal (RM) (d = 0.53) and 60% RM (d = 1.02) during hip thrusts, while the SQG showed higher barbell velocity at 80% RM (d = -0.7) during back squats. These results may be useful for strength and conditioning coaches working with adolescent female soccer athletes, since both strengthening exercises improved performance in different ways due to the nature of the exercise